2021
DOI: 10.1101/2021.06.17.21258268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enrichment of SARM1 alleles encoding variants with constitutively hyperactive NADase in patients with ALS and other motor nerve disorders

Abstract: SARM1, a protein with critical NADase activity, is a central executioner in a conserved programme of axon degeneration. We describe eight rare missense or in-frame microdeletion human SARM1 variant alleles, in patients with amyotrophic lateral sclerosis (ALS), hereditary spastic paraparesis (HSP), or other motor nerve disorders, that alter the SARM1 auto-inhibitory ARM domain and constitutively hyperactivate SARM1 NADase activity. The constitutive NADase activities of six of the variants are at least as high a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 76 publications
1
17
0
Order By: Relevance
“…Our data also have many implications for the development of therapies for axonopathies. Animal and cell culture data strongly implicate SARM1-dependent axon loss in some peripheral neuropathies, glaucoma, Parkinson's disease and other conditions [1,3,59] and human genetic studies support its involvement in rare axonopathies involving NMNAT2 mutation [7,8] and in ALS [5,6]. This, together with the complete rescue of axons by SARM1 removal when the pathway is very specifically activated [10,20] has led to considerable focus on inhibiting and knocking down SARM1 as a therapeutic strategy [3,28,32,60].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our data also have many implications for the development of therapies for axonopathies. Animal and cell culture data strongly implicate SARM1-dependent axon loss in some peripheral neuropathies, glaucoma, Parkinson's disease and other conditions [1,3,59] and human genetic studies support its involvement in rare axonopathies involving NMNAT2 mutation [7,8] and in ALS [5,6]. This, together with the complete rescue of axons by SARM1 removal when the pathway is very specifically activated [10,20] has led to considerable focus on inhibiting and knocking down SARM1 as a therapeutic strategy [3,28,32,60].…”
Section: Discussionmentioning
confidence: 99%
“…Wallerian degeneration occurs when axons are physically transected but it is now clear that the underlying programmed axon death mechanism is also activated by many toxins, gene mutations or metabolic disruption [3,4]. SARM1 is also constitutively hyperactivated by mutations associated with ALS [5,6]. The crucial step common to many of these is loss of functional NMNAT2 from axons, an enzyme synthesising the dinucleotide NAD from its precursor mononucleotide NMN.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, stillborn fetuses with biallelic NMNAT2 null mutations were also reported (Lukacs et al, 2019). Following earlier human studies implicating this pathway in ALS by GWAS association to the SARM1 chromosomal locus and loss of potential SARM1 regulator STMN2 in human induced pluripotent stem cell (hiPSC)derived motor neurons (Fogh et al, 2014;van Rheenen et al, 2016;Klim et al, 2019;Melamed et al, 2019), recent work has revealed that human SARM1 variant alleles that hyperactivate SARM1 NADase function and enhance neuronal vulnerability are enriched in patients with sporadic ALS, hereditary spastic paraplegia and other motor nerve disorders (Bloom et al, 2021;Gilley et al, 2021). Whether further mutations to NMNAT2, SARM1 or other proteins involved in the Wallerian degeneration pathway represent risk factors for other neurological diseases in living humans, is yet to be seen.…”
Section: Links To Diseases and Future Therapiesmentioning
confidence: 98%